Review of Regime Maps of Steam-Submerged Direct Contact Condensation - Du, Yu; Yan, Xiao; Zang, Jinguang; Zhang, Yan (Frontiers in Energy Research, 2020)
Steam-submerged direct contact condensation is widely applied in industry fields. As it has the enormous capacity of heat and mass transfer, the phenomenon is widely used in nuclear engineering equipment which are related to safety, such as the suppression pool in the boiling water reactor (BWR). It is important to understand the regime map when we study this phenomenon because the characteristics of heat and mass transfer vary with the regime, including the characteristic of the interface of steam and water. Lots of researchers have investigated the regime of steam-submerged direct contact condensation. Different researchers have developed different regime maps with their own or other people's experimental data. This article reviews the present research on the regime maps and discusses further efforts on the important phenomenon.